Identifying Constraints in the Social Entrepreneurship Ecosystem of India : A developing country context - Sharma, Venus (2015)
Social entrepreneurs are faced with multiple challenges which are further amplified in resource deficit environment of developing economies. However, there has been a limited examination of the barriers and limitations present in social enterprise ecosystem from the developing country context. This research takes the case of India to identify the constraints which influence decision making and impact of the social enterprises, as perceived by various active participants of the social enterprise ecosystem. It reveals three major categories of challenges present in both macro and micro environment of the social enterprise ecosystem of India and further provides potential solutions to the challenges identified.